Preliminary experience with a novel intraoperative fluorescence imaging technique to evaluate the patency of bypass grafts in total arterial revascularization. - Taggart, D; Choudhary, B; Anastasiadis, K; Abu-Omar, Y; Balacumaraswami, L; Pigott, D (2003)
BACKGROUND: Early graft failure is a common cause of cardiac morbidity and mortality after coronary artery bypass grafting (CABG), and there is particular concern about graft patency in off-pump CABG. We describe our preliminary experience with a novel imaging technique (the SPY system), based on fluorescence of Indocyanine Green when exposed to near infrared light, for the intraoperative assessment of coronary graft patency. METHODS: Graft patency was assessed in patients undergoing off-pump and on-pump total arterial revascularization. The imaging technique requires injection of a 1-mL bolus of Indocyanine Green into the central venous line, followed by imaging with the SPY system. RESULTS: We assessed intraoperative graft patency in 213 conduits in 84 patients (mean, 2.54 grafts per patient), of which, 65 (77%) were done off-pump. It took approximately 3 minutes to image each graft. Skeletonized conduits provided better visualization than pedicled ones. Fluorescence, confirming graft patency, was observed in all but four (1.9%) conduits in 4 (5%) patients. In these latter cases, graft revision was necessitated. CONCLUSIONS: Fluorescence imaging of coronary grafts using the SPY is a uniquely simple, safe, noninvasive, and reproducible technique for intraoperative confirmation of graft patency. In 4 patients, it necessitated revision of the initial intraoperative procedure. Quantification of graft flow would enhance the value of the system.